Tradisi Sorong Serah dalam Prosesi Perkawinan Masyarakat Adat Sasak: Sebuah Tinjauan ‘Urf (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2023)
This study is intended to explain the sorong serah tradition in the marriage customs of the Sasak people of Lombok, within the framework of Islamic law. This study uses a qualitative approach. Data was collected through observation and interviews. This study uses the analysis of 'urf which is one of the arguments in determining Islamic law, with the consideration that 'urf is a theory that is more relevant to aspects of tradition, culture or customs. The results of this study indicate that the implementation of aji krame in the sorong serah tradition uses refined language which is the highest stratum in the Sasak language, not mantras that contain shirk as some people suspect. The use of high language in aji krame is a custom that does not conflict with Islamic law, in fact there are many conformities there.